Walk 14 DOWN THE CIRCUM-BAIKAL RAILWAY - Lidin, Konstantin; Grigoryeva, Elena; Demkov, Sergey; Chertilov, Alexei; Buinov, Alexei; Vedernikova, Tatyana; Antipin, Lyutsian (project baikal, 2014)
Walk 14 DOWN THE CIRCUM-BAIKAL RAILWAY Sketch Redesign of the Sverdlovsky Market in Irkutsk "Glazkovo Shopping Arcade" Church of Sts. Apostles Peter and Pavel in Irkutsk – a Rare Monument of Architecture in Pribaikalie Redesign of the Church of Sts. Peter and Pavel in Irkutsk St. Nicholas and St. Innokenty Temple in Irkutsk Redesign of St. Nicholas and St. Innokenty Church Railway Station Building Projects of the Railway Station and the Hotel Facilities